2014
DOI: 10.1186/s12955-014-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life ratings in dementia care – a cross-sectional study to identify factors associated with proxy-ratings

Abstract: ObjectiveQuality of life (QoL) is one major outcome parameter in the care for people with dementia (PwD); however, their assessment is lacking a gold standard. The purpose of this study was to evaluate potential factors associated with nurse-rated quality of life of PwD in nursing homes in Berlin, Germany.MethodAn explorative cross-sectional study was performed in five nursing homes to evaluate QoL. Nurses rated the QoL for all residents with dementia by completing two different standardised assessments (ADRQL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
3
36
0
2
Order By: Relevance
“…The differences in the rating of QOL between self-report and proxy report generally depend on variables such as depressive symptoms and severity of dementia and should be recognized [55,61,62,63,64]. The QUALIDEM was developed to measure QOL in persons with dementia; however, observational instruments always have the possibility of observer bias [65].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the rating of QOL between self-report and proxy report generally depend on variables such as depressive symptoms and severity of dementia and should be recognized [55,61,62,63,64]. The QUALIDEM was developed to measure QOL in persons with dementia; however, observational instruments always have the possibility of observer bias [65].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are nine studies did not find any relationship between demographic characteristics and QoL (Andersen et al, 2004;Grske et al, 2014;Moyle et al, 2015;Monteiro et al, 2014;Sloane et al, 2005;Winzelberg et al, 2005;Wetzels et al, 2010;Salvador et al, 2000), other studies found that higher education (Marventano et al, 2015;Li et al, 2012), males (Woods et al, 2014;Barca et al 2011), white (Black et al, 2012), widowed (Samus et al, 2005) and extroverted characteristic (Li et al, 2012) tended to be positively associated with better QoL for elderly people with dementia. Moreover, Banerjee et al (2005) found that QoL of people with dementia showed decline as with the increasing age, while Mjørud et al (2014) indicated that the QoL was worse among the youngest (<79) and oldest (>90) people with dementia.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…It is assumed that such influence may be more evident among elderly people with severe dementia. Occurrence of challenging behaviours such as physical aggressive behaviours are recognised as another adverse predictor in QoL rating (Grske et al, 2014;Winzelberg et al, 2005;. 20 The influences of physical activities on QoL for elderly people with dementia were identified by five studies (Potter et al, 2011;Beerens et al, 2014;Letts et al, 2011;Silberfeld et al, 2002;Orpwood et al, 2007).…”
Section: Physical Factorsmentioning
confidence: 99%
“…Researchers have rightly questioned the accuracy of recall of agitated behaviours by staff members working in care homes, due to the impact of caregiver burden. Care staff reporting a lower burden have been found to provide higher quality of life ratings than those experiencing more caregiver burden (Graske et al, 2014). One possible explanation for this is that care staff experiencing more burden also expect residents to be experiencing this burden (Graske et al, 2014).…”
Section: Discussionmentioning
confidence: 99%